An Error Analysis of Complex Clause Production in Islamic-Themed Essays by Islamic Religious Education Students - Ilham; Verawati; Asyir Fadillah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Palangkaraya, 2026)
The mastery of complex clauses is a critical prerequisite for academic writing in English, particularly for students of Islamic Religious Education who must integrate foreign grammatical structures with semantically dense Islamic terminology. This descriptive qualitative study, grounded in the Error Analysis framework, aims to identify error patterns in the production of noun clauses and adjective clauses in Islamic-themed essays and to interpret the underlying causal factors. Primary data were drawn from 15 Mid-Term Examination answer sheets produced by second-semester PAI students, while supporting data were collected through a Focus Group Discussion with six purposively selected students. Document analysis revealed that the most dominant errors occurred in spelling and mechanics, followed by misordering, omission, misformation, and subject-verb disagreement. A further notable finding was the emergence of avoidance strategy, whereby students consistently simplified their ideas into short, discrete sentences to circumvent the risk of errors in complex clause formation. FGD data indicated that students used Indonesian as a cognitive mediator prior to composing in English, while Islamic terminology compounded the cognitive load of the composition process. These findings point to a persistent gap between students' declarative grammatical knowledge and their productive competence in free writing. This study recommends an instructional approach that integrates pre-teaching of Islamic domain vocabulary, scaffolded complex clause production practice, and the reinforcement of students' linguistic self-efficacy.